Perilaku Aktor dalam Merespon Inisiatif Hijau pada Industri Makanan dan Minuman: Sebuah Scoping Review - Kus Ariningsih, Paulina (Jurnal Rekayasa Sistem Industri, 2024)
Understanding the actors' behavior is an essential step to recognizing the standpoint of each actor to generate a strategy that facilitates collaboration and healthy coopetition in creating a green and sustainable impact. By defining a suitable strategy, the optimization of collaboration and coopetition in a sustainable food and beverage supply chain can be performed through game theory optimization. Therefore, this study aims to understand the description of the actors' behaviors corresponding to sustainable incentives in the food and beverage industry in existing game-theory optimization literature. This study was carried out by conducting a literature scoping of two significant databases: Scopus and Web of Science. 1816 articles were identified in the initial selection, and 25 were deeply evaluated and mapped. The literature scoping review shows that the supply chain's performance and interaction are related to the actors' actions, which have an independent interest, though they share a common desire to maximize its benefits. The main financial incentives are found in the game theory literature. However, the other incentives are not yet explored thoroughly. In the near future, it is suggested to conduct research on formulation of ethical and social incentives in order to be utilized in game theory optimization.